Feasibility study of a gasoline station - Hontanosas, Carlos Raymund (College of Engineering, 1993)
The main objective of this project is to determine the overall feasibility of establishing a gasoline station. This was accomplished by evaluating the project's desirability in consideration with its market, technical and financial aspects. The concepts and principles of the various aspects are applied in the study as deemed necessary by the project team members. The group decided to franchise a gasoline station since it was observed that there is an increasing traffic volume hence demands in the Bicutan interchange area. This was confirmed when majority of the respondents of the survey conducted by the study group during the marketing phase of study, agreed to the idea of establishing a new gasoline station in the said area. Most of the information the team has gathered were based on personal interviews conducted with Pilipinas Shell. Some of the data, however, like the fuel products consumption for the past years and population size was based on the figures provided by the Department of Energy and the Philippine Statistical Office, respectively. A survey was also conducted in the market study portion to determine the target markets expected reception of the project's concept. Financial figures were gathered through canvassing and interviews. Market Aspect: The study shows that there is an increasing demand for the various fuel products except regular gasoline. This is verified from the forecasted figures computed. The survey also shows that 9 out of 10 residents of the target area are in favor of establishing a new gasoline station. This supports the team's choice of location. Technical: The study shows that the cost of establishing the gasoline station is minimal since the franchising company, Pilipinas Shell, will shoulder the cost of the structure. It also justified the various technical requirements like number of pumping stations required, and the tank as well as the station size. Financial: The study shows that the project will be earning a steady income of more than a million per year with a capital outlay of just slightly over one million. This means that the project cost can be recovered within one year of operation. Socio-Economic: The study shows that the project can benefit the community by providing employment to the local residents. It also serves as a catalyst for the continuing commercialization of the target market.